Kinesthetic treatment strategies for facial sequelae after resection of left petroclival meningioma through telerehabilitation. : Abordaje Kinesico de las Sincinesias mediante telerehabilitacion (Journal on studies and research of academic knowledge, 2024)
The Covid-19 Pandemic has represented a challenge for the treatment and monitoring of patients in general, but even more so, in the population of people with facial paralysis, which motivated the implementation of telerehabilitation as a treatment and monitoring strategy for these patients.  The follow-up was carried out on a 51-year-old patient with facial paralysis of one month's duration, presence of synkinesis and facial spasms, post-surgical sequelae of left petroclival meningioma resection, treated during the period August 2021, April 2022. Kinesic therapy sessions were carried out through telerehabilitation, due to COVID-19 restrictions, therapeutic resources were based on patient education during the session, re-education and facial inhibition exercises in front of a mirror, massage therapy and stretching, the patient was also provided with explanatory short videos with each technique performed during the session. The House Brackman scale and the Synkinesis Assessment Questionnaire (SAQ) were used to assess the degree of paralysis and synkinesis. At the initial evaluation according to the House Brackman scale, grade V paralysis was observed (severe dysfunction, total paralysis, asymmetry in rest and movement) and a score of 41 was obtained on the SAQ. After 8 months of kinesic treatment, the following results were obtained; HB: grade 3 paralysis (paresis and mild to moderate dysfunction) and 25 on the SAQ. Although facial symmetry, complete occlusion of the eyes, fluid containment in the mouth and improvement in facial function were achieved according to the aforementioned scales, hemifacial spasms continue to be present and the patient reported that these increase in frequency and intensity with fatigue and stress.